2023
DOI: 10.3390/ijerph20075301
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alcohol Consumption during the COVID-19 Pandemic: Evidence from Wisconsin

Abstract: Alcohol consumption often increases in times of stress such as disease outbreaks. Wisconsin has historically ranked as one of the heaviest drinking states in the United States with a persistent drinking culture. Few studies have documented the impact of the COVID-19 pandemic on alcohol consumption after the first few months of the pandemic. The primary aim of this study is to identify factors related to changes in drinking at three timepoints during the first eighteen months of the pandemic. Survey data was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…Table 6 provides a comparison between our research methodology, results, and the location where the survey was conducted with those of other studies carried out in various geographical regions. It should be noted that similar top predictors for increased alcohol consumption were identified in both our study and the study conducted by Pomazal et al 14 . It is worth mentioning that while our analysis was based on a survey conducted in Michigan, the study by Pomazal et al 14 was conducted in Wisconsin.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Table 6 provides a comparison between our research methodology, results, and the location where the survey was conducted with those of other studies carried out in various geographical regions. It should be noted that similar top predictors for increased alcohol consumption were identified in both our study and the study conducted by Pomazal et al 14 . It is worth mentioning that while our analysis was based on a survey conducted in Michigan, the study by Pomazal et al 14 was conducted in Wisconsin.…”
Section: Discussionsupporting
confidence: 90%
“…It should be noted that similar top predictors for increased alcohol consumption were identified in both our study and the study conducted by Pomazal et al 14 . It is worth mentioning that while our analysis was based on a survey conducted in Michigan, the study by Pomazal et al 14 was conducted in Wisconsin. Although our study identified children at home as the top predictor of alcohol consumption increase during the pandemic, the study by Pomazal et al 14 also identified it as an important factor.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations